Pemanfaatan Media Pembelajaran Berbasis Android Pada Anak Usia Dini - Rahmadani, Kurniati; Masamah, Mamah (Universitas Lampung, 2023)
Currently the world of education continues to develop along with the times and technological developments. Currently, with the help of technology, teachers will be facilitated in the teaching and learning process, one of which is by using technology as a learning medium. In this all-digital era, learning has been carried out in the form of interactive media which of course is adapted to the needs of children. So this research is focused on developing children's cognitive knowledge through Android-based interactive media so that they can develop children's thinking skills and can be used anywhere. The method that researchers use is descriptive qualitative. Data collection techniques in this study are observation, interviews, and documentation. With the target of this research are students of Pancasila Kb PAUD with an age range of 5-6 years. This android media contains animal diversity material accompanied by information from these animals and is equipped with animal sounds, there are quizzes in the form of questions to test students' understanding.Kata kunci: Android, Interactive media, children, animals